Evaluating Motor Performance with the Bruininks-Oseretsky Test of Motor Proficiency in impoverished Pakistani Children - Zehra Habib Hasan; Fariha Shaheen; Arjumand Rizvi; Jelena Obradovic; Aisha Khan Yousafzai (Journal of the Pakistan Medical Association, 2021)
Objectives: Children’s cognitive and motor development is intertwined with their nutritional status and compromised by an impoverished environment. This study examined a modified Bruininks Oseretsky Test of motor proficiency - Brief Form (BOT2 BF) to evaluate its sensitivity in identifying motor differences secondary to malnutrition and poverty. Methods: Data was drawn from 1058 children who participated in a responsive-stimulation and nutrition intervention in the first two years of life. Outcome measures included motor development assessed via BOT2 BF, child anthropometry (height- and weight-for-age), according to the World Health Organization growth reference charts and household economic and demographic information collected using a family report questionnaire. Results: Mann Whitney U test was significant for malnutrition, socio-economic status and maternal literacy at p< 0.05, for a 6-item motor composite of BOT2 BF. Psychometric properties of the BOT2 BF were robust for this Pakistani cohort. Conclusion: A 6-item motor composite of BOT2 BF is a reliable tool to measure motor performance in Pakistani pre-school children Continuous....